Synergistic catalysis of satellite single-atomic Fe sites and RuFe nanoclusters on N-rich carbon nanoflowers for boosting oxygen reduction - Wang, Chen-Yang; Ren, Cheng-Zhi; Fang, Ke-Ming; Feng, Jiu-Ju; Shi, Yacheng; Gao, Yi-Jing; Wang, Ai-Jun (Journal of colloid and interface science, 2025)
[Display omitted] Improving oxygen reduction activity and stability of catalysts is an effective strategy, which can be achieved by fine-regulating electronic structure of active centers and adsorption behavior of intermediates through synergistic effects and multiple coordination between the metal clusters and single-atom sites. Herein, we introduce a dual-linker-engaged self-assembly strategy to construct three-dimensional nitrogen-rich carbon nanoflowers with a simultaneous loading of satellite Fe single atoms (SAs) and RuFe nanoclusters (NCs) by high-temperature pyrolysis. X-ray absorption fine structure characterizations and DFT calculations confirm that the synergistic interactions between single-atomic Fe sites (coordinated as Fe-N4) and RuFe NCs significantly enhance oxygen reduction reaction (ORR) activity. The cooperative effect between the RuFe NCs and the Fe-N4 sites optimizes the adsorption energy of the reaction intermediates and lowers the energy barrier of the potential determining step, thereby improving the reaction kinetics. Leveraging these structural characteristics, the Fe/RuFe@N-CNFs exhibits excellent ORR performance, with a half-wave potential of 0.87 V in a 0.1 M KOH solution. When applied in the home-made Zn-air battery, the Fe/RuFe@N-CNFs delivers a high peak power density of 110.5 mW cm−2 and long-term cycle stability, which reveals its promising application in energy storage devices. This study presents a cooperative modulation strategy between the SAs and NCs, providing a feasible approach for design and synthesis of high-performance catalysts with precisely controlled active centers.